Assessment of the Role of Private Enterprises /Small Businesses on Economic Growth (A Study of Some Selected SME’S in Imo State, Nigeria) - Esiagu, Lilian N.; Okoroji, Lazarus I.; Anyanwu, Julius O. (International Journal of Economics, Business and Management Studies, 2016)
The quest for self-reliance and employment generation has not only given rise to private enterprises, but has also necessitated the need to diversify the Nigerian economy for an increased significant growth. This study therefore is on the role of private enterprises/ small scale businesses on economic growth of Nigeria. Imo State was used for this study. Specific research objectives and research questions were formulated in line with the problems of this study. Literatures related to this study were also reviewed. The study adopted a survey approach and the result of the study shows that small scale businesses increased employment generation opportunities; it also shows that there is significant relationship between small scale businesses and Nigeria’s economic development. The study therefore concluded with some recommendations which include; government should provide financial opportunity for small business owners, seminars and workshops should be organized for business owners for requisite skills and many other recommendations.